FORMATION AND RECOGNITION OF COPYRIGHT IN UKRAINE - Шуст, Наталія Борисівна; Смородина, Алла Євгенівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: definition of the formation and recognition in the copyright of personal property and non-property rights of intellectual property. Methods: the methodological basis of the research was formed by general scientific methods of cognition, as well as substantive scientific knowledge with the help of which the lawful use of the norm of the Civil Code of Ukraine in the context of personal property and non-property rights of intellectual property. Results: the initial principle of the proposed scientific research is the development of theoretical legal constructions of the history of the development of copyright, taking into account the adoption of the Civil Code of Ukraine which carried out the restructuring of the system of intellectual property rights, proposed the unification of approaches to terminology and protection of objects of intellectual property law. Discussion: modern changes in society determine not only the emergence of new legal mechanisms, but also the need to change the paradigm of legal thinking and redefine the theoretical foundations of the law as a whole and also actualize the need to identify the causes of legal evolution and develop ways of progressive development of law in Civil law, Ukrainian legislation on copyright.